2016
DOI: 10.14355/ijrsa.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Forest and Juniperus Phoenicea Decline in Al Jabal Al Akhdar Using NDVI-Remote Sensing and GIS Data (2006-2013)

Abstract: Al Jabal al Akhdar, Locally known as the Green Mountain, located in Cyrenaica on the north east coast of Libya. It is a limestone plateau with maximum altitudes of about 900 meters, holds the highest plant density and species diversity within the country. Among these plants is the Juniperus phoenicea (JP) which covers about 70% of this mountain. It has been sharply deteriorated by unidentified causes over large scales. In this work, we have used remote sensing and GIS data to monitor vegetation vigor variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…58, No.1 (2018) between the longitudes 20° 35′ E to 23° 15′ E and latitudes 30° 58′ N to 32° 56′ N in the North-East of Libya between Benghazi and Darnah ( Fig. 2) (Suleiman et al, 2016). This Jabal (mountain)…”
Section: Study Area and Materialsmentioning
confidence: 91%
“…58, No.1 (2018) between the longitudes 20° 35′ E to 23° 15′ E and latitudes 30° 58′ N to 32° 56′ N in the North-East of Libya between Benghazi and Darnah ( Fig. 2) (Suleiman et al, 2016). This Jabal (mountain)…”
Section: Study Area and Materialsmentioning
confidence: 91%
“…Researchers employ a variety of methods, including visual inspection, sampling for laboratory analysis, and remote sensing by satellite imaging, to identify and examine dieback in these trees (Castellaneta, Rita, Camarero, Colangelo, & Ripullone, 2022: Valeriano, Gazol, Colangelo, González de Andrés, & Camarero, 2021: Suleiman, Mohamed, Hamad, & Elmehdy, 2016. In other studies, dieback in Phoenician juniper in Libya and the Arabian Peninsula similarly showed no sign of fungal infection and has been attributed to drought, induced by climate change and associated changes in microclimate (Fisher 2000).…”
Section: ‫انتحقيق‬mentioning
confidence: 99%
“…1). The collected mosses were found growing, on shaded coarse soil between rocks where water flows under trees below Wadi Kouf old bridge (Fig.2 (Suleiman et al, 2016). The Wadi Al-Kouf area consists of rocks and stones with high and low water levels and is rich in arborescent seed plants as: Ceratonia siliqua L., Juniperus phoenicea L., Olea europaea L., Quercus coccifera L., Pistacia lentiscus L. and Phillyrea latifolia L. Wadi Al-Kouf area is part of Al-Jabal AlAkhdar region.…”
Section: Materials and Study Areamentioning
confidence: 99%
“…The Al-Jabal Al-Akhdar is a limestone plateau 700 to 870 m above sea level with an undulating surface which tips gently to the south, stretches between the longitudes 20° 35′ E to 23° 15′ E and latitudes 30° 58′ N to 32° 56′ N in the North-East of Libya between Benghazi and Darnah ( Fig. 1) (Suleiman et al, 2016). This Jabal (mountain) is covered by arching Plateau built of upper Cretaceous and Tertiary sediments of limestone, subordinate dolomites and marls.…”
Section: Materials and Study Areamentioning
confidence: 99%